Modified coronally advanced flap with and without orthodontic button application in management of multiple proximate gingival recession defects: A randomized clinical trial - Sumedh Khobragade; Abhay Kolte; Rajashri Kolte; Tushar Shrirao; Anushree Potey (Wolters Kluwer Medknow Publications, 2016)
Background: Gingival recession indicates oral display of the root surface due to apical movement of gingival margin. Coronally advanced flap (CAF) is often used periodontal plastic surgical technique to accomplish root coverage. The purpose of this clinical trial is to assess and compare the effectiveness of modified CAF with orthodontic button application (CAF*B) and without orthodontic button application (CAF) for the correction of multiple recession defects. Materials and Methods: Twenty patients exhibiting bilateral multiple proximate Millers Class I and/or Class II gingival recession defects were included in the study. Each set of proximate recession defects was designated randomly to test or control group. Control group was treated by CAF alone and test group by CAF*B. Baseline and postoperative clinical parameters at 2, 4, and 6 months time interval were recorded. Results: Mean root coverage percentage from baseline to 6 months in control group was 78.30% ± 20.75% and in test group was 92.23% ± 15.6%. Complete root coverage was 43.8% in control group and 77.47% in test group. Visual analog scale pain measurements did not reveal any difference among both the groups. Patient satisfaction with esthetics was very high in CAF*B group when compared with CAF group. Conclusion: Both treatment modalities, i.e., CAF and CAF*B are effectual in the treatment of proximate Miller's Class I and Class II gingival recession defects, but CAF*B showed significantly superior clinical results.